Book review: Arthur W. Frank (2010). 'Letting Stories Breathe: A Socio-Narratology.' Chicago: University of Chicago Press - Mildorf, Jarmila (Biography)

Risk assessment for better Identity Management in pervasive environments - Arias Cabarcos, Patricia (Ninth Annual IEEE International Conference on Pervasive Computing and Communications, PerCom 2011, 21-25 March 2011, Seattle, WA, USA, Workshop Proceedings)

Edgar Salins Wiederentdeckung von Friedrich List: Die Legitimation der „Anschaulichen Theorie“ durch die Suche nach Vordenkern - Schönhärl, Korinna (Transfer und Wiederaneignung von Wissen)

Übergangscoaching mit Jugendlichen. Wirkfaktoren aus Sicht der Coachingnehmer beim Übergang von der Schule in die Ausbildung - Wiethoff, Christoph

Discrete mechanics and optimal control: Structure preserving integration for the optimal control of mechanical systems - Ober-Blöbaum, Sina (Proceedings of Oberwolfach Reports ''Geometric Numerical Integration'')

A variational approach to multirate integration for constrained systems - Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Oberwolfach Reports ''Applied Dynamics and Geometric Mechanics'')

Discrete mechanics and optimal control: an analysis - Ober-Blöbaum, Sina; Junge, O.; Marsden, J. E. (Control, Optimisation and Calculus of Variations)

A variational approach to multirate integration for constrained systems - Leyendecker, S.; Ober-Blöbaum, Sina (Paul Fisette and Jean-Claude Samin, editors, ECCOMAS Thematic Conference: Multibody Dynamics: Computational Methods and Applications)

Discrete Mechanics and Optimal Control and its Application to a Double Pendulum on a Cart - Timmermann, Julia; Khatab, Shaady; Ober-Blöbaum, Sina; Trächtler, Ansgar (18th IFAC World Congress 2011)

Berechnung optimaler Stromprofile für einen 6-phasigen, geschalteten Reluktanzantrieb - Flaßkamp, K.; Ober-Blöbaum, Sina; Ringkamp, M.; Schneider, T.; Schulte, C.; Böcker, J. (8. Paderborner Workshop Entwurf mechatronischer Systeme)

Variational formulation and optimal control of hybrid Lagrangian systems - Flaßkamp, K.; Ober-Blöbaum, Sina (HSCC '11: 14th International Conference on Hybrid Systems: Computation and Control)

Variational multirate integration of constrained dynamics - Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Variational integrators for electric circuits - Ober-Blöbaum, Sina; Tao, M.; Owhadi, H. (Proceedings of Applied Mathematics and Mechanics)

Mesh refinement strategies for spacecraft trajectory optimization using discrete mechanics and optimal control - Moore, A.; Ober-Blöbaum, Sina; Marsden, J.E. (21st AAS/AIAA Space Flight Mechanics Meeting)

A variational approach to multirate integration for constrained systems (ECCOMAS Thematic Conference: Multibody Dynamics: Computational Methods and Applications)

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela

Complexity-induced production and inventory cost in consumer goods supply chain - Danne, Christoph; Dangelmaier, Wilhelm; H{\, Petra

CO²-Emmission aware pareto optimization for international transportation with time tables - Xue, Yudong; Irohara, Takashi; Klöpper, Benjamin; Pater, Jan-Patrick

Efficiency in automotive assembly lines - Sommer-Dittrich, Thomas; Ziegler, M; Altemeier, Simon

Inventory relocation for overlapping disaster settigs in humanitarian operations - Rottkemper, Beate; Fischer, Kathrin; Blecken, Alexander; Danne, Christoph (OR Spectrum)
The number and scale of humanitarian operations has significantly increased during the past decades due to the rising number of humanitarian emergencies and natural disasters worldwide. Therefore, the development of appropriate planning methods for optimization of the respective supply chains is constantly growing in importance. A specific problem in the context of humanitarian operations is the supply of relief items to the affected areas after the occurrende of a sudden change in demand or supply, for example, due to an epidemic or to unexpected shortages, durng an ongoing humanitarian action. When such overlapping disasters occur, goods must be relocated to existing depots in a way which enables rapid suppply to regions with new and urgent demand. At the same time, ongoing operations have to continue, i. e., the other regions should not suffer from shortages, and possible future emergencies must be taken into account. This is a planning situation under uncertainty as it is not known in advance if and where a disruption - and hence additional demand - will occur. In this paper, an optimization model for such situations is developed based n penalty costs for non-satishied demand. A rolling horizon approach for solving the model is presented, and it is shown that taking into account the possibility of future disruptions can helb to balance inventories and to reduce total non-served demand.